Design, synthesis and biological evaluation of novel 1, 3-diarylpyrazoles as cyclooxygenase inhibitors, antiplatelet and anticancer agents. Issue 5 (6th April 2018) - Inceler, Nazan; Ozkan, Yesim; Turan, Nilufer Nermin; Kahraman, Deniz Cansen; Cetin-Atalay, Rengul; Baytas, Sultan Nacak
Abstract : ( E )-3-[3-(Pyridin-3/4-yl)-1-(phenyl/sulfonylmethylphenyl)-1 H -pyrazol-4-yl]acrylamides were synthesized and their COX-1 and COX-2 inhibitory, antiplatelet and cytotoxic activities were evaluated. Abstract : With the aim of achieving new compounds possessing both anti-inflammatory and antiplatelet activities, we synthesized ( E )-3-[3-(pyridin-3/4-yl)-1-(phenyl/sulfonylmethylphenyl)-1 H -pyrazol-4-yl]acrylamides, and evaluated their COX-1 and COX-2 inhibitory and antiplatelet activities. Since COX-2 inhibitory and antiplatelet compounds have anticancer potential, we also screened their antiproliferative effects against three human cancer cell lines. Compounds5n, 5p, 5s, 10d, 10g and10i were determined as dual COX-2 inhibitor/antiplatelet compounds. Compound10h appeared to be a compound that exhibited antiplatelet activity without inhibiting the COX enzyme. Compounds5h, 10a and10i were the most effective derivatives which displayed antiproliferative activity against Huh7, MCF7 and HCT116 cells. Particularly, compound10i, as the compound exhibiting the highest cytotoxic, antiplatelet and COX-2 inhibitory activity, was remarkable.